Tony solves the linear equation 3(x - 3) + 2x + 9 = 2x + 2(x - 1) using the step shown below.
Step 1: 3x - 3 + 2x + 9 = 2x + 2x - 1
Step 2: 5x + 6 = 4x - 1
Step 3: 5x - 4x = -1 - 6
Step 4: x= -7
b
Oc
Od
He incorrectly applied the addition and subtraction properties of equality.
He distributed incorrectly.
He incorrectly applied the multiplication and division properties of equality.
He incorrectly combined like terms.

Respuesta :

Answer:

He distributed incorrectly.

Step-by-step explanation:

To solve  3(x - 3) + 2x + 9 = 2x + 2(x - 1)

Opening the parenthesis will yield

3x - 9  + 2x + 9 = 2x + 2x - 2

5x  =  4x - 2

Subtract 4x from both-side of the equation

5x-4x  =  4x -4x- 2

x = -2

The mistake he made is;

3(x - 3) = 3x - 9    

Not  3x-3

Also

2(x - 1) = 2x -2  

Not  2x-1